(untitled) (International Journal of Engineering and Computer Science, 2015)
With the speedy growth in mobile communication, mobile phone has become a common part for most people. Short messaging service (SMS) is a convenient technology for a user to get the needed information delivered on demand. Different SMS based FAQ retrieval systems are available in which user gives query in SMS language and retrieve ranked result answers from FAQ database where FAQ database contains questions and answers for these questions which are specified by experts. This paper describes a survey of various SMS based FAQ retrieval systems for various domains.